How To Build Customer Loyalty: Through Customer Experience, Perceived Price, And Customer Satisfaction - et. al., Edhie Budi Setiawan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The competition to get the highest Market Share among Low-Cost Carrier airlines in Indonesia is getting fierce. Airlines are competing to offer prices that are appropriate for passengers to perceive them in this era of tariff wars. The degree of satisfaction that is felt is needed to get loyal customers. The purpose of this research is to analyze the impact of customer experience and perceived price on customer loyalty through customer satisfaction. The method of analysis in this study uses the SEM-PLS (Structural Equation Model - Partial Least Square) method with 250 respondents taken by purposive sampling. The result of this research is there is effect positive and significant between customer experience on customer satisfaction and customer loyalty, also there is effect of perceived price on customer satisfaction and customer loyalty. Airlines must pay attention to the services provided to create a memorable experience for passengers and adjust prices to be accepted by passengers.